Determination of reinforcer value in rats with an adjusting-delay choice procedure involving a correspondence between location and amount of reinforcement - Ridge, Thomas; Linwick, Daniel (My University, 2006)
Many models of reinforcement value predict that an animal should value a large delayed reinforcer more than a small immediate reinforcer. However, as the delay between choices and presentation of the large reinforcer increases, eventually, an animal should value the small reinforcer more highly. The current experiment employed a discrete-trials choice procedure to test these predictions.
Color poster with text describing research conducted by Thomas Ridge, advised by Dr. Daniel C. Linwick (University of Wisconsin-River Falls) that assessed self-control in rats and evaluated a quantitative model that included a delay-of-reinforcement parameter.
Keywords: Reinforcement (Psychology); Conditioned response; Behaviorism (Psychology); Self-control; Reinforcement value; Operant behavior; Self-control in rats; Reinforcer value; Delay of reinforcement